CHEMICAL CATALYSIS OF NITRATE REDUCTION BY IRON (II) - Ottley C.J.; Davison W.; Edmunds W.M. (My University, 1997)
Experiments have been conducted to investigate the chemical reduction of nitrate under conditions relevant to the often low organic carbon environment of groundwaters. At pH 8 and 20+/-2°C, in the presence of Cu(II), NO-3 was chemically reduced by Fe(II) to NH+4 with an average stoichiometric liberation of 8 protons. The rate of the reaction systematically increased with pH in the range pH 7-8.5. The half-life for nitrate reduction, t12, was inversely related to the total molar copper concentration, [CuT], by the equation log t12 = -1.35 log [CuT] - 2.616, for all measured values of t12 from 23 min to 15 days. At the Cu(II) concentrations used of 7 x 10-6-10-3 M, Cu was present mainly as a solid phase, either adsorbed to the surfaces of precipitated iron oxides or as a saturated solid. It is this solid phase copper rather than Cu2+ in solution which is catalytically active. Neither magnetite, which was formed as a product of the reaction, nor freshly prepared lepidocrocite catalysed the reaction, but goethite did. Although traces of oxygen accelerated the reaction, at higher partial pressures (>0.01 atm) the reduction of nitrate was inhibited, probably due to competition between NO-3 and O2 for Fe(II). Appreciable catalytic effects were also observed for solid phase forms of Ag(I), Cd(II), Ni(II), Hg(II), and Pb(II). Mn(II) enhanced the rate slightly, and there was evidence for slow abiotic reduction in the absence of any added metal catalysts. These results suggest that the chemical reduction of nitrate at catalytic concentrations and temperatures appropriate to groundwater conditions is feasible on a timescale of months to years.